Urban ruins : memorial value and contemporary role - Pilia, Elisa (Berlin : DOM publishers, 2019)
This monograph discusses the role that ruins play in urban centers in terms of their meaning, testimony, and value, and the opportunities they provide. After an outline of historical and contemporary approaches, with a special analysis of British and Italian approaches, Elisa Pilia puts forward a methodology for the investigation of the strategic values of such artifacts, and ideas for their potential contribution to a sustainable requalification of historic urban cores. The protocol is tested on the historical center of Cagliari, a midsized port city on the southern coast of the island of Sardinia, Italy, where the remains left by aerial bombardment during the Second World War are still a dramatic part of the controversial European debate on how to reuse ruins.
Includes bibliographical references (pages 213-221).
Keywords: Ruined buildings; Ruins, Modern; City planning; Excavations (Archaeology); Ruined buildings -- Conservation and restoration; City planning -- Italy -- Cagliari; Ruins, Modern -- Italy -- Cagliari; Ruined buildings -- Italy -- Cagliari; Urban archaeology; Landscape assessment; Cagliari (Italy) -- Antiquities; Ruins, Modern; Ruined buildings; Excavations (Archaeology); City planning; Antiquities; Landscape assessment; Urban archaeology; Italy -- Cagliari